Integrated reproductive health services: the perspectives of providers - P. Maharaj (AOSIS, 2004)
With the advent of the AIDS epidemic the focus of family planning programmes has shifted from an emphasis on pregnancy prevention to include disease prevention. The move towards integration has meant a major re-orientation in the role of health providers. This article seeks to expand knowledge about the implementation of integrated services from the perspective of providers. It focuses more specifically on the provider's perceptions and experiences of integrated services. A range of methods is used to obtain information from providers, including an inventory of health facilities, in-depth interviews and focus group discussions. The results suggest that the majority of providers expressed favourable attitudes to integrated services. Integrated services are seen as a more client centred approach. However, there is a lack of clarity about the precise form that integration should take. As a result, providers seem more comfortable with the traditional focus on family planning and maternal and child health than sexually transmitted infections.